Sources of State Income in Al-Mawardi's View - Santika, Ganjar; Janwari, Yadi; Jubaedah, Dedah (Yayasan Meira Visi Persada, 2024)
A country that has succeeded in creating people's welfare is a characteristic of a successful country, one of its successes is increasing the quality of life of the people which is closely related to economic life. This notion of State Revenue has been voiced for a long time, one of whom is Muslim scholar Al-Mawardi stated that State revenue comes from zakat, ghanimah, jizyah and kharaj, while if the State reduces the budget then revenue can be generated from taxes and public loans, in more detail the author will explained about Al-Mawardi's thoughts on State Revenue.